Leveraging Strategic Management and Digital Marketing for Sustainable Competitive Advantage in Indonesia's Tourism Industry - Dian Sudiantini; Eteh Resa Asyifa; Debby CH Rende (Dinasti International Journal of Education Management and Social Science, 2026)
This study investigates how strategic management and digital marketing integration creates sustainable competitive advantage in Indonesia's tourism industry. While digital technology adoption is widespread, the strategic alignment of digital initiatives with core business strategies remains underexamined in emerging economy tourism contexts. Employing an explanatory sequential mixed-methods design with 102 survey respondents and 18 industry experts, this research demonstrates that strategic-digital integration significantly influences customer engagement and business performance. Although 94% of businesses utilize digital marketing tools, only 62% fully integrate them with strategic objectives—revealing a critical implementation gap. The study extends Dynamic Capabilities Theory and Resource-Based View by conceptualizing "digital strategic fit" and "digital strategic resilience." Findings suggest competitive advantage emerges not from technology adoption alone, but from strategic reconfiguration aligning digital capabilities with organizational objectives.